Clinical Observation of a Child with Astrocytoma - T.V. Sirenko; O.V. Piontkovskaya; A.A. Khotsenko; O.N. Plakhotnaya; A.V. Postnikov; T.A. Khalturina (Zaslavsky O.Yu., 2013)
The article deals with the result of clinical observation of a child with astrocytoma and lesion of subependymal zones of lateral ventricles of the brain and gray tuber.